Psychological determinants of declining interest in the future professional activity of senior students - Akhtaeva, N. S.; Sundetova, G. O.; Tastanova А. A.; Sadykova N. М.; Boltayeva A. М.; Sailinova, K. K. (ҚазҰУ Хабаршысы. Психология және әлеуметтану сериясы, 2019)
The article deals with psychological determinants that influences to the reduction in interest in the professional choice of future specialists. The statistics of graduates of universities of the Republic of Kazakhstan and in Almaty is presented. It should be noted that the numbers tend to increase every year. Many students after graduation from high school do not work in their specialty. Statistics on this issue is of great interest for psychology: how to motivate students to achieve success in learning activities; how to motivate teachers to maintain interest in their chosen profession. The results of the study showed that a decrease in interest in future professional activity among senior students is influenced by the lack of clearly defined professional intentions, a superficially formed understanding of the future profession and a lack of knowledge about it (namely, knowledge of the physical and mental health requirements of the chosen profession ). Students who have a tendency to interest decrease in their future profession have a lower level of adaptation than students who are satisfied with their choice (namely, adaptedness in the study group). Solving the problem requires a clear, competent and scientificallybased vocational guidance. This article does not reveal all the psychological reasons that may affect the decline in interest in the future profession, but it gives grounds for further research on the problem under consideration. Key words: professional selfdetermination, selfdevelopment, professional work, motivation.